Fault detection and analysis of bistable rotaxane molecular electronic switch - A simulation approach. Issue 1 (1st January 2018) - S, Devisree; Kumar, Anand
ABSTRACT: As the transistor size approaches nano dimension, short channel effects become dominant in micro devices, leading to an incessant struggle to keep pace with Moore's law. This paved way to development of newer technologies like molecular electronics. The self-assembled bottom-up approach makes molecular switches more prone to defects than micro devices. The widely studied molecular switches are mechanically coupled and this paper deals with bistable rotaxane. Feasibility of using bistable rotaxane as a molecular electronic device is analysed in terms of total molecular energy, energy band gap, ionisation energy and distance between ring and dumbbell. Total molecular energy is the vital criteria that decides the feasibility of using a self-assembled rotaxane as a switch. Rotaxane has a band gap of 1.44 eV at Ground State Co-Conformer (GSCC) and hence acting as a semiconductor. Ionisation energy and position of ring are also important in deciding the switching activity. Due to process variations during self-assembly, ring can localise anywhere over the dumbbell and it may leads to a faulty switch. This work describes a method to verify the switching action of bistable rotaxane through simulation. Testing method described here is carried out before the actual manufacturing of nano crossbar and hence cost effective.